Automated personnel-assets-consumables-drug tracking in ambulance services for more effective and efficient medical emergency interventions. Issue 127 (April 2016) - Utku, Semih; Özcanhan, Mehmet Hilal; Unluturk, Mehmet Suleyman
Highlights: Convenient and rapid inventory control of the PACD in the ambulance. Alarm generation for device maintenance and line replacement of outdated drugs. Missing PACD identification and alarm generation in case of asset removals. Automatic patient information transfer and sharing (hospital–ambulance). Prevention of unprovisioned ambulance dispatch due to depleted or missing PACD. Abstract: Patient delivery time is no longer considered as the only critical factor, in ambulatory services. Presently, five clinical performance indicators are used to decide patient satisfaction. Unfortunately, the emergency ambulance services in rapidly growing metropolitan areas do not meet current satisfaction expectations; because of human errors in the management of the objects onboard the ambulances. But, human involvement in the information management of emergency interventions can be reduced by electronic tracking of personnel, assets, consumables and drugs (PACD) carried in the ambulances. Electronic tracking needs the support of automation software, which should be integrated to the overall hospital information system. Our work presents a complete solution based on a centralized database supported by radio frequency identification (RFID) and bluetooth low energy (BLE) identification and tracking technologies. Each object in an ambulance is identified and tracked by the best suited technology. The automated identification and tracking reduces manual paper documentation and frees the personnel to better focus on medical activities. The presence and amounts of the PACD are automatically monitored, warning about their depletion, non-presence or maintenance dates. The computerized two way hospital–ambulance communication link provides information sharing and instantaneous feedback for better and faster diagnosis decisions. A fully implemented system is presented, with detailed hardware and software descriptions. The benefits and the clinical outcomes of the proposed system are discussed, which lead to improved personnel efficiency and more effective interventions.